Energy response and identification efficiency of CsI(Tl) crystals irradiated with energetic protons. (June 2020) - Frosin, C; Barlini, S; Poggi, G; Casini, G; Bini, M; Stefanini, A A; Valdré, S; Gruyer, D; Ciemala, M; Maj, A; Ziebliński, M; Sowicki, B; et al.
Abstract: Proton energy calibration and identification efficiency of few Thallium activated Cesium Iodide (CsI(Tl)) crystals of the FAZIA detection system, have been studied in the range 59-180 MeV by using the proton beam delivered by the cyclotron of the CCB (Cyclotron Center Bronowice) facility. We observe that the light output versus energy is linear in the lower investigated energy range while showing a deviation from linearity above 140 MeV. The effects of proton induced nuclear reactions and multiple scattering causing incomplete energy deposition (IED) events have been identified and estimated via Pulse Shape Analysis in CsI(Tl) crystals. The measured experimental efficiency for proton identification in the examined energy range is then compared with GEANT4 simulations. For a centered collimated irradiation on the crystal, and at the highest measured energy, the resulting experimental efficiency value is about 70%.